ANALYSIS THE VALUE OF ENVIRONMENTAL AWARENESS IN DESCRIPTIVE TEXT IN SECONDARY SCHOOL ENGLISH BOOKS - Ulfa Gusnaini; Totok Hari Prasetiyo; Imro’atul Husna Afriani; St. Shabibatul Rohmah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Environmental awareness is an activity carried out to maintain and care for nature that is already available. This activity certainly requires sufficient attention so that the earth is protected from disasters that occur due to a lack of awareness of the environment. a sense of care can be planted from a small scope such as in the family and school environment. Books are one of the media used as teaching materials during class learning. Textbooks are also one of the major influences on student behavior. This study aims to identify how environmental awareness is contained in English textbooks at the senior high school level in Banyuwangi. This study used CDA(Critical Discourse Analysis) to investigate the value of environmental concerns contained in textbooks. In this research, the descriptive qualitative method was used by using random sampling in English textbooks for classes X and XI of senior high school. The results of this study found that the value of environmental concern was still lacking where researchers found three descriptive texts in class X and one descriptive text in class XI.